Canal preparation and filling techniques do not influence the fracture resistance of extensively damaged teeth - Santini, Manuela Favarin; Rippe, Marília Pivetta [UNESP]; Franciscatto, Gisele Jung; da Rosa, Ricardo Abreu; Valandro, Luiz Felipe; Só, Marcus Vinícius Reis; Bier, Carlos Alexandre Souza (FapUNIFESP (SciELO), 2014)
The purpose of this study was to assess the fracture resistance of extensively damaged teeth after two root canal preparation techniques (hand and rotary files) and after two filling techniques (active and passive compaction). Sixty-eight maxillary canines roots with an apical diameter equal to that of a #25 K-file were embedded in acrylic resin and the periodontal ligament was simulated by using a polyether impression material. The roots were randomly distributed into four groups (n=17): hand preparation and active compaction (HA), hand preparation and passive compaction (HP), rotary preparation and active compaction (RA), and rotary preparation and passive compaction (RP). All roots were restored with glass fiber post and metallic crown. The specimens were mechanically cycled (500,000 cycles, 45°, 37°C, 133 N, 2 Hz) and then subjected to a fracture resistance test. A single blinded examiner analyzed the external root surface and classified the failure pattern as favorable or unfavorable. The fracture resistance values ranged between 621.15 N (HP) and 785.71 N (HA). However, the Kruskal-Wallis test did not reveal differences in the fracture resistance values among the four groups (p =0.247). Under the tested conditions, root canal preparation and filling techniques had no influence on the fracture resistance of extensively damaged teeth restored with fiber post and metallic crown.
Keywords: Glass fiber post; Root canal filling techniques; Root canal preparation techniques; Vertical root fracture